The Un-meeting approach to stimulate collaborative adult learning: an application for clinical research professionals. Issue 1 (21st July 2021) - Jones, Carolynn Thomas; Lane, Aric; Shah, Arti; Carter, Karen; Lackey, Russell; Kolb, Robert
Abstract: We used a Zoom Un-meeting as an educational approach to provide experienced clinical research professional (CRP) adult learners a collaborative learning space to learn more about current issues for academic medical center (AMC) clinical research workforce development and collaborate on solution finding. CRPs operationalize the conduct of clinical trials and represent a significant brain trust for the Clinical and Translational Science (CTSA) consortium hubs with their vast knowledge base, extensive experience, understanding of relevant institutional policy, organizational culture, and clinical research operations. Un-meetings are an intentionally organized and coordinated group activity that encourages participants to focus on a topic and incorporate an open flow of ideas through brainstorming and an open discussion format, setting the stage for future collaborative action. We divided topics into a series of six consecutive monthly Un-meeting Zoom workshops. Ultimately, one resulting output from the meeting was the Center for Leading Innovation and Collaborations (CLIC) synergy paper award to support continued collaborative work. Currently, work teams have emerged to analyze qualitative data from brainstorming and breakout session recordings and to identify small-group activities. We describe this adult learning tool as valuable for exploring issues of AMC CRP professional development. This approach encouraged creative/critical thinking and opportunities for leadership, team science, and problem-solving among participants.